Multiple sclerosis and neuropsychiatric disorders during the COVID-19 pandemic. Literature review - K. Brasas; V. Lileikytė; D. Mickevičienė (Neurologijos seminarai)
Since the spread of COVID-19 infection worldwide in December 2019, quarantine has been initiated to stop human contact and thus limit the spread of the disease. However, a decrease in human contact and visits to doctors has led to another problem in patients with chronic diseases, especially those with multiple sclerosis, such as worsening of neuropsychological status, depression, increased stress levels, insomnia, and decreased physical activity. In this article, we review the scientific work of other authors on the impact of the COVID-19 pandemic on the neuropsychological condition of patients with multiple sclerosis and possible solutions to this problem.